Isoflavone Protects the Renal Tissue of Diabetic Ovariectomized Rats via PPAR-γ - Ferraz Carbonel, Adriana Aparecida; da Silva, Rafael André [UNESP]; de Souza Ferreira, Luiz Philipe; Vieira, Renata Ramos; Dos Santos Simões, Ricardo; da Silva Sasso, Gisela Rodrigues; de Jesus Simões, Manuel; Soares Junior, José Maria; Azevedo Lima, Patrícia Daniele; Borges, Fernanda Teixeira (MDPI, 2022)
Diabetes associated with post-menopause is related to a worse condition of kidney dis-ease. Taking into consideration that this disorder may be regulated by estrogenic mediators, we evaluated the renal protective effect of isoflavone. We investigated the role of the PPARγ in the pathogenesis of the disease. For this study, we used diabetic female rats in a postmenopausal model through ovariectomy. The animals were treated with isoflavone or 17β-estradiol. A dosage was ad-ministered to bring on blood glycemia, and through immunohistochemistry, we evaluated the im-munoreactivity of PPARγ in the endometrium and renal tissue. We analyzed the immunoreactivity of renal injury molecule KIM-1 and the collagen and glycogen densities in the kidney. Through bioinformatics analysis, we observed PPARγ and COL1A1 gene expression under the influence of different glucose doses. In particular, we observed that isoflavone and 17β-estradiol regulate blood glycemia. Renal injury was inhibited by isoflavone, observed by a reduction in KIM-1, along with glycogen accumulation. These benefits of isoflavone may be associated with PPARγ overexpression in the kidneys and endometrium of diabetic ovariectomized rats.
Keywords: diabetes; isoflavone; kidney; postmenopausal; PPARγ